Materials and devices for high‐density, high‐throughput micro‐electrocorticography arrays - Yang Xie; Yanxiu Peng; Jinhong Guo; Muyang Liu; Bozhen Zhang; Lan Yin; He Ding; Xing Sheng (Fundamental Research)
The pursuit of precisely recording and localizing neural activities in brain cortical regions drives the development of advanced electrocorticography (ECoG) devices. Remarkable progress has led to the emergence of micro-ECoG (µECoG) devices with sub-millimeter resolutions. This review presents the current research status, development directions, potential innovations and applications of high-density, high-throughput µECoG devices. First, we summarize the challenges associated with accurately recording single or multiple neurons using existing µECoG devices, including passive multielectrode and active transistor arrays. Second, we focus on cutting-edge advancements in passive µECoG devices by discussing the design principles and fabrication strategies to optimize three key parameters: impedance, mechanical flexibility, and biocompatibility. Furthermore, recent findings highlight the need for further research and development in active transistor arrays, including silicon, metal oxide, and solution-gated transistors. These active transistor arrays have the potential to unlock the capabilities of high-density, high-throughput µECoG devices and overcome the limitations of passive multielectrode arrays. The review explores the potential innovations and applications of µECoG devices, showcasing their effectiveness for both brain science research and clinical applications.